Inequities in Therapy for Infantile Spasms: A Call to Action. Issue 1 (28th April 2022) - Baumer, Fiona M.; Mytinger, John R.; Neville, Kerri; Briscoe Abath, Christina; Gutierrez, Camilo A.; Numis, Adam L.; Harini, Chellamani; He, Zihuai; Hussain, Shaun A.; Berg, Anne T.; Chu, Catherine J.; Gaillard, William D.; et al.
Abstract : Objective: The aim of this study was to determine whether selection of treatment for children with infantile spasms (IS) varies by race/ethnicity. Methods: The prospective US National Infantile Spasms Consortium database includes children with IS treated from 2012 to 2018. We examined the relationship between race/ethnicity and receipt of standard IS therapy (prednisolone, adrenocorticotropic hormone, vigabatrin), adjusting for demographic and clinical variables using logistic regression. Our primary outcome was treatment course, which considered therapy prescribed for the first and, when needed, the second IS treatment together. Results: Of 555 children, 324 (58%) were non‐Hispanic white, 55 (10%) non‐Hispanic Black, 24 (4%) non‐Hispanic Asian, 80 (14%) Hispanic, and 72 (13%) other/unknown. Most (398, 72%) received a standard treatment course. Insurance type, geographic location, history of prematurity, prior seizures, developmental delay or regression, abnormal head circumference, hypsarrhythmia, and IS etiologies were associated with standard therapy. In adjusted models, non‐Hispanic Black children had lower odds of receiving a standard treatment course compared with non‐Hispanic white children (odds ratio [OR], 0.42; 95% confidence interval [CI], 0.20–0.89; p = 0.02). Adjusted models also showed that children with public (vs. private) insurance had lower odds of receiving standard therapy for treatment 1 (OR, 0.42; CI, 0.21–0.84; p = 0.01). Interpretation: Non‐Hispanic Black children were more often treated with non‐standard IS therapies than non‐Hispanic white children. Likewise, children with public (vs. private) insurance were less likely to receive standard therapies. Investigating drivers of inequities, and understanding the impact of racism on treatment decisions, are critical next steps to improve care for patients with IS. ANN NEUROL 2022;92:32–44